Religiosity and Green Entrepreneurship Motivation: The Role of Commitment to Environment - Maisaroh; Aidha Trisanti; Arief Darmawan (Journal of Management and Entrepreneurship Research)
Objective: This quantitative study investigates the key predictors of motivation for green entrepreneurship. Research Design & Methods: Religiosity is identified as an independent variable, green entrepreneurship motivation as the dependent variable, while commitment to environment is the mediating variable. The sampling method was purposive random sampling from 160 SME Leaders in Yogyakarta. Data analysis used SEM PLS. Findings: The findings showed that all hypotheses are supported. Religiosity positively impacts green entrepreneurship motivation and commitment to environment, while commitment to environment positively impacts green entrepreneurship motivation. Besides that, the connection between religiosity and green entrepreneurship motivation is mediated by commitment to environment. Implications and Recommendations: The result suggests that religiosity directly affects both the drive to engage in green entrepreneurship and the commitment to environmental responsibility; the commitment to the environment serves as a key mediator, amplifying the overall motivation. A limitation of this study is its cross-sectional design, which restricts the ability to generalize the results. Therefore, future research could focus on testing the model with a larger sample and exploring religious motivation as a distinct predictor of green entrepreneurship motivation. Contribution & Value Added: Conceptually, this research contributes to existing model antecedents of green entrepreneurship motivation that have rarely been studied before, and highlights the roles of religiosity and commitment to environment. Practically, this finding opens up opportunities for policymakers to develop programs that can help MSME actors leverage their religious motivation to create more sustainable businesses.